EPR Spectral, Magnetic and Electrochemical Studies of Copper-Vanadyl Trinuclear Complexes - Annapoorani, S.; Krishnan, C.N. (Asian Journal of Chemistry, 2014)
In this paper, we report the synthesis and characterization of several amben- and amben-type ligands and their copper-vanadium trinuclear complexes, which are derived from 2-aminobenzaldehyde and several diamines. The complexes are characterized by variable temperature EPR spectral, magnetic studies and cyclic voltammetric studies. The complexes are found to have the formula [VO(CuL)2]SO4. The EPR spectral and magnetic studies suggest the weak interaction between the terminal copper ions and the central oxovanadium(IV) ion. Cyclic voltammetric studies confirm the presence of copper and vanadium ions in the complexes.